X mapping in man: evidence against direct measurable linkage between ocular albinism and deutan colour blindness. Issue 4 (August 1976) - Pearce, W G; Sanger, R
Abstract : A Newfoundland kindred in which ocular albinism and deutan colour blindness are segregating provides strong evidence against the loci for these two X-borne characters being within direct measurable distance of each other.